Clinical resolution of periodontitis among diabetic patients with chronic periodontitis co-morbidity under medical-dental coordinated care: a preliminary study in Kuantan - Yaacob, Munirah; Tin, Myo Han; Ismail, Razida; Sidek, Sorayah; Hari, Padmini; Md Aris, Mohd Aznan; Osman, Iskandar Firzada; Thuraiappah, Mahendran; Abdullah, Fa’iza; Than, Tun Sein; Saub, Roslan (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2017)
Clinical resolution of periodontitis (CRP) of type-2 diabetic patients with chronic periodontitis (T2DM-PD) after receiving non-surgical periodontal treatment (NSPT) has been reported in the previous studies. This study aimed to evaluate CRP of T2DM-PD under medicaldental coordinated care (M-DCC). Materials and Methods: A 6-months follow-up quasi-experimental study was conducted among 20 subjects who received M-DCC in 2016. M-DCC included standard diabetic care provided by medical professional from 3 health clinics and NSPT provided by periodontal specialists from two periodontal specialist clinics. Target glycemic control achievement (TGCA) HbA1c 6.5% was assessed at baseline and 6 months after NSPT. Clinical resolution of PD was measured in terms of BPE, BOP %, CAL(mm), PPD(mm), PPD 4mm, PPD =4 mm and PPD 6mm at baseline, 3 and 6 months. Paired simple t test and ANOVA F test were applied to infer clinical resolution of periodontitis and its relation to TGCA. Results: Mean (SD) of average BPE at baseline, 3- and 6-months were 3.52(0.34), 3.12(0.33) and 3(0.45) with (p<0.05); average PPD(mm) were 3.33(0.5), 3.23(0.75) and 2.73(0.57) with (p<0.05); PPD(%) 4mm were 71.03(12.33), 82.77(9.9) and 85.85 (8.9) with (p<0.05); PPD(%) =4 mm were 27.94(11.9), 16.97(10.01) and 13.71(9.1) with (p<0.05) ; PPD(%) 6mm were 8.04(4.32), 2.66(2.3) and 1.87(2.32) with (p<0.05). Significant resolution of BPE, CAL(mm) and PPD(mm) was noticed among two subjects who has changed from uncontrolled TGCA to controlled TGCA. Conclusion(s): CRP and TGCA results have verified the effectiveness of M-DCC. A further clinical control trial with adequate sample size needs to confirm the results of the present study.